FENOMENA JUDI ONLINE DI KALANGAN MAHASISWA : PENEGAKAN HUKUM, FAKTOR, DAMPAK DAN UPAYA PENCEGAHANNYA - Ratihpuspita Krisnowo; Annisa Nur Halizah; Missel Ester (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
Students are one of the parties interested in being able to get involved in online gambling. Because this is a phenomenon that is trending among them. The current era of globalization provides an easy opportunity for students to be able to earn income or pocket money in an instant way through online gambling. The lack and limited supervision and enforcement for perpetrators of online gambling crimes among students has a bad impact that eventually becomes a habit so that it can harm future generations in Indonesia. This research uses a literature law research method or normative law research method, normative juridical approach and conceptual approach. Gambling is regulated in Article 303 and Article 303 of the Criminal Code, this is after the issuance of Law Number 7 of 1974 concerning the Control of Gambling where the criminal threat for gambling is aggravated, further related to online gambling is contained in the provisions regulated in Article 27 paragraph (2) of Law Number 11 of 2008 concerning Information and Electronic Transactions, This violation is regulated in the provisions of Article 45 Paragraph (2) of the ITE Law, which is punishable by imprisonment for a maximum of 6 (six) years and/or a maximum fine of 1 billion rupiah. The factors that affect why gambling can occur among students are economic and social factors, environmental factors and perception factors. The impact is a decrease in achievement and interest in learning, financial or economic impact, a decrease in spiritual/religious values, a decrease in social values, psychological disturbances and addiction. The approach taken is preventive, repressive, persuasive and curative. In addition, other things that are done are education about risks and negative impacts, awareness campaigns, involvement of parents, family and friends, development of positive alternatives, counseling and emotional support, cooperation with the government, training for lecturers and monitoring and supervision of students online activities. Thus, if viewed from the formulation contained in the criminal law, it means that it is very clear that gambling is prohibited by legal norms because it has met the formulation of the elements of a criminal act, for that it can be subject to criminal sanctions whose implementation is processed in accordance with the criminal procedure law and the support and cooperation of all elements of society can be a means to anticipate online gambling among students.